Nationalist Character Education of Javanese Language Children's Literary Texts in the Panjebar Semangat Magazine - Nur Hasan, Latif; Pairin, Udjang; Adipitoyo, Sugeng; Wijoyanto, Danang; Edliani Lestari, Tri (Proceeding of International Joint Conference on UNESA, 2024)
Children's literature is critical in inheriting literature, especially Javanese literature, because the use of Javanese in children begins to fade. Not only as a literary heritage, children's literature contains character education needed for children's development. One of them is character education that supports the Pancasila Student Profile is Nationalist, which can be found in many children's literary texts in Panjebar Semangat magazine". This study aims to reveal the value of nationalist education in the boy's discourse. The approach used in this study is an approach to the text that is only focused on the works (texts) of children's literature reading. The object of this research study is Javanese children's literature published in the Panjebar Semangat Javanese Magazine. The results of the nationalist character analysis found three types of nationalist character education, namely; 1) maintain the nation's cultural wealth, 2) love the motherland, 3) and respect diversity. The children's literary texts describe the three character educations implicitly and explicitly.